The first record of late Permian tetrapods from Namibia - Mocke, Helke B; Kammerer, Christian F; Smith, Roger M H; Marsicano, Claudia A (Evolutionary Studies Institute, 2023)
The entire Omingonde Formation in Namibia was previously assigned a Triassic age based on the fossil tetrapod fauna discovered southwest of theWaterberg Plateau. However, recently repatriated and newly collected material suggests that the lowermost part of the Omingonde Formation includes late Permian strata, equivalent in age to the upper Endothiodon Assemblage Zone of the South African Karoo Basin. In this study,we document the first record of late Permian tetrapod fossils from Namibia, and provide brief descriptions of a gorgonopsian skull collected at Mount Etjo in 1996 and the skull of a small dicynodont collected at the same site in 2019, referable to cf. Tropidostoma. This material confirms that there is need for better understanding of the stratigraphy of the Etjo Mountain area, in particular the position and nature of the unconformity between strata of the Permian Endothiodon and the Triassic Cynognathus assemblage zones.
Keywords: Endothiodon Assemblage Zone; biostratigraphy; Tropidostoma; gorgonopsian; Late Palaeozoic; southern Africa